Dampak Penyaluran Kredit Melalui BPR Sari Madu terhadap Distribusi Pendapatan Masyarakat di Kota Bangkinang Kabupaten Kampar - Shorea khaswarina (Jurnal Sagu, 2009)
The aim of this research was to identify and analyze income distribution of credit recipients at Bangkinang City before and after receiving credit. This research was conducted at Bangkinang City, Kampar district. Income distribution of credit recipients was analyzed by Gini Ratio. The result showed that the revolving credit of Sari Madu BPR did not significantly change recipient’s income distribution but lower gini ratio indicated that the income distribution tended to distribute more evenly. According to the t-test, utilization of the credit in economic activities had significant effect on recipiuent’s net income, so the credit was valuable to help society starting their own businesses.